Penerapan Metode Demonstrasi Bangun Ruang Pembelajaran Matematika Untuk Meningkatkan Hasil Belajar Siswa Kelas II di MI Nahdlatul Ulama’ 01 Purwosari - Zuhaida, Khusna; Auliya, Fadhilatul Fithri; Nisa', Khoirun; Hanik, Elya Umi (Lembaga Yasin AlSys, 2021)
This study aims to improve the learning outcomes of students' mathematical geometric shapes by using demonstration methods and using spatial media. This classroom action research was carried out in 1 cycle with four stages, namely: planning, implementation, observation, and reflection. The subjects of this study were students of class II MI Nahdlatul Ulama 01 Purwosari Kudus as many as 33 students. This research uses descriptive qualitative and quantitative descriptive analysis techniques. The results of this study indicate that the use of the spatial demonstration method can improve student learning outcomes which are marked by an increase in completeness, namely pre-cycle with an average value of 69, while in the first cycle with an average value of 85 and declared successful.